Perceived impact of an interprofessional education program on community resilience: an exploratory study. Issue 5 (16th May 2013) - Slack, Marion Kimball; McEwen, Marylyn Morris
Abstract: The purpose of this study was to explore the perceived impact of an interprofessional education (IPE) program for health sciences students on two culturally diverse, underserved communities. A community resilience/capacity framework, consisting of catalysts (primarily the creation of awareness) and capital components: human (workforce development), social (networking and empowerment) and economic (volunteer labor and money spent by the program), provided the conceptual underpinnings for the study. Focus groups with stakeholders in two communities, one rural and one metropolitan, were audio-recorded, transcribed and analyzed by categorizing data according to each capital component. In addition to the concepts contained in the capacity framework a new category, informational capital (data specific to the community) emerged during the analysis. We suggest that by acting as a catalyst a community based interprofessional program can affect components of community resilience/capacity, primarily human, social, and informational capital. Using the community resilience/capacity framework facilitated exploration of the perceived impact of an educational program on one rural and one urban underserved community beyond assessing student outcomes or number of clients served.